The effect of low-viscosity sediments on the dynamics and accretionary style of subduction margins - A. E. Pusok; A. E. Pusok; A. E. Pusok; D. R. Stegman; M. Kerr (Solid Earth, 2022)
Observations of sediments at subduction margins appear to divide them into two classes: accretionary and erosive. Accretionary margins are dominated by accretion of thick piles of sediments (>1 km) from the subducting plate, while tectonic erosion is favored in regions with little or no sedimentary cover (<1 km). The consequences of the two styles of margins for subduction dynamics remain poorly resolved. In this study, we used 2-D numerical simulations of subduction to investigate how low-viscosity sediments influence subduction dynamics and margin type through plate coupling. We vary the thickness and viscosity of the sediment layer entering subduction, the thickness of the upper plate, and the driving velocity of the subducting plate (i.e., kinematic boundary conditions). Diagnostic parameters are extracted automatically from numerical simulations to analyze the dynamics and differentiate between modes of subduction margin. We identify three margin types based on the extent of viscous coupling in the sediment layer at the subduction interface: (a) tectonic coupling margin, (b) low-angle accretionary wedge margin, and (c) high-angle accretionary wedge margin. In the tectonic coupling case – analogous to an erosive margin – high-viscosity or thin-layer sediments increase coupling at the interface. On the other hand, when the viscous coupling is reduced, sediments are scrapped off the subducting slab to form an accretionary wedge. Models that develop tectonic coupling margins show small radii of curvature, slow convergence rates, and thin subduction interfaces, while models with accretionary margins show large radii of curvature, faster convergence rates, and dynamic accretionary wedges. These diagnostic parameters are then linked with observations of present-day subduction zones.